Operational Analysis of the Culminating Phase of the Battle of the Atlantic: A German fait accompli - Gordon, Jeffrey D. (2002)
The Battle of the Atlantic was the dominating factor all through the war. Never for one moment could we forget that everything happened elsewhere, on land, at sea, or in the air, depended ultimately on its outcome, and amid all other cares we viewed its changing fortunes day by day with hope or apprehension. The Atlantic proved to be the decisive grounds on which Britain's ability to wage a sustained war against the axis powers rested. The period of August 1942 through May 1943 has proven to be the critical period in the Battle of the Atlantic. During this phase of the battle, the allies turned the tables on a surge in German U-boat successes and rising confidence and precipitated such a severe reversal of fortune that and Commander in Chief (CinC) of the German Navy and U-boat arm, Grand Admiral Karl Doenitz, was driven to the conclusion that a complete withdrawal of U-boats from the North Atlantic was required. This paper will examine the operational aspects of the German offensive in the Battle of the Atlantic during the culminating phase in the first half of 1943 and the factors that led to the German collapse. The lessons learned from the German perspective can be instructive in how a unified approach to this battle would have prolonged Germany's ability to truly affect the allied shipping, and may have influenced the final outcome. The original document contains color images.